2020
DOI: 10.3390/ijerph17249579
|View full text |Cite
|
Sign up to set email alerts
|

Are Reallocations between Sedentary Behaviour and Physical Activity Associated with Better Sleep in Adults Aged 55+ Years? An Isotemporal Substitution Analysis

Abstract: Physical activity has been proposed as an effective alternative treatment option for the increasing occurrence of sleep problems in older adults. Although higher physical activity levels are associated with better sleep, the association between specific physical activity intensities and sedentary behaviour (SB) with sleep remains unclear. This study examines the associations of statistically modelled time reallocations between sedentary time and different physical activity intensities with sleep outcomes using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Different types of activities may interact with each other, thereby in uencing frailty in older adults. Regular physical activity promotes relaxation and energy consumption [51], and has been proposed as an effective non-pharmacological treatment option to improve sleep in older adults [52]. Existing studies have shown that physical activity is associated with sleep quality in older adults [53], with those engaging in higher levels of physical activity exhibiting better sleep quality [54] and regularity [55].…”
Section: Introductionmentioning
confidence: 99%
“…Different types of activities may interact with each other, thereby in uencing frailty in older adults. Regular physical activity promotes relaxation and energy consumption [51], and has been proposed as an effective non-pharmacological treatment option to improve sleep in older adults [52]. Existing studies have shown that physical activity is associated with sleep quality in older adults [53], with those engaging in higher levels of physical activity exhibiting better sleep quality [54] and regularity [55].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these substitutional relationships between SB, light-intensity physical activity (LPA), and moderate-to-vigorous physical activity (MVPA) need to be considered when examining how a particular behaviour may impact sleep quality. To the best of our knowledge, however, only one previous study has examined the associations of reallocating time between sedentary time and different physical activity intensities on sleep outcomes among adults aged 55 years and older 22 . There is a lack of studies exploring these substitutional relationships during middle-aged adulthood, a life stage when age-related health, including sleep quality, begins 23 .…”
Section: Introductionmentioning
confidence: 99%
“…12 A study found that low handgrip strength was independently associated with poor sleep quality in middle-aged and older adults. 13 Although the association between SB, PA, and sleep has been investigated in the literature, 14,15 studies examining the relationship between dynapenia and SB, PA, and sleep, especially their effects when assessing the reallocation of the exposure time of older individuals to these activities, are lacking. Therefore, investigating sleep hour time, MVPA, and SB in relation to dynapenia is relevant; an isotemporal substitution modeling shows the ability not only to control the effect between activities but also the effect of substitutions of time spent, reducing the heterogeneity of associations, thus facilitating public health recommendations.…”
Section: Introductionmentioning
confidence: 99%